New Mexico vegetation, past, present, and future - Dick-Peddie, William A; Moir, William H.; Spellenberg, Richard (UNM Press Albuqueque, New Mexico, 1992)
A comprehensive study of the biological history and evolution of New Mexico's vegetation, including a detailed account of the distribution of plant communities in the state today. For each vegetation type, the principal plant species are discussed, with special attention given to describing how plants sharing a common location interact and, in particular, how human activity impacts on each type. With 29 color plates, and a map of the state's vegetation, including vegetation types not found on existing maps. Annotation copyright Book News, Inc. Portland, Or.
64246
Keywords: Botany; Plant Communities; Phytogeography; Ecology; New Mexico